2021
DOI: 10.1039/d1gc00901j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical upgrading of biomass-derived 5-hydroxymethylfurfural and furfural over oxygen vacancy-rich NiCoMn-layered double hydroxides nanosheets

Abstract: Rational design of low-cost and active electrocatalysts is crucial for upgrading of biomass-derived chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 54 publications
3
78
0
Order By: Relevance
“…This study provided an effective way to generate cationic vacancies and demonstrated the decisive role of cationic vacancies in the electrocatalytic oxidation of HMF. Meanwhile, the catalysts of ternary NiCoMn‐layered double hydroxides (NiCoMn‐LDHs) nanosheets with abundant oxygen vacancies have been prepared to selectively electrocatalytic HMF‐to‐FDCA oxidation (91.7 % yield of FDCA) [55] . The mechanism indicated that the ultrathin nanosheets exposed more Co‐NiOOH active sites and were accompanied by oxygen vacancies, which facilitated the synergistic oxidation of HMF in Co−Ni and Mn 2+ states.…”
Section: Electrocatalytic Conversion Of Hmfmentioning
confidence: 99%
“…This study provided an effective way to generate cationic vacancies and demonstrated the decisive role of cationic vacancies in the electrocatalytic oxidation of HMF. Meanwhile, the catalysts of ternary NiCoMn‐layered double hydroxides (NiCoMn‐LDHs) nanosheets with abundant oxygen vacancies have been prepared to selectively electrocatalytic HMF‐to‐FDCA oxidation (91.7 % yield of FDCA) [55] . The mechanism indicated that the ultrathin nanosheets exposed more Co‐NiOOH active sites and were accompanied by oxygen vacancies, which facilitated the synergistic oxidation of HMF in Co−Ni and Mn 2+ states.…”
Section: Electrocatalytic Conversion Of Hmfmentioning
confidence: 99%
“…Biomass, the largest carbon-neutral renewable source on Earth, is considered a promising alternative to our dependence on limited fossil fuel sources and the associated environmental issues [1][2][3][4][5][6]. Combustion and anaerobic digestion are adopted extensively to treat biomass; however, these techniques are inefficient and possess problems.…”
Section: Introductionmentioning
confidence: 99%
“…Catalyst development play an important role in achieving this goal. Over the last a few decades, different types of catalysts (e.g., metal nanoparticles, enzyme, acidic or basic candidates) have been frequently designed and investigated ( Alonso et al, 2013 ; Nanda et al, 2016 ; Hu et al, 2019 ; Liu et al, 2021 ). This special issue concentrates on the pretreatment of biomass using enzymes, anaerobic digestion of naive source, various factors on the thermal pyrolysis, value-added chemicals synthesis and degradation.…”
Section: Introductionmentioning
confidence: 99%